Given the expression:
![(3^2)^3\cdot3^x=(3^7\cdot3^3)/(3^(11))](https://img.qammunity.org/2023/formulas/mathematics/high-school/2wfdy6vq921yetwiy8tyuz8o87tuq0firf.png)
notice that on the left side, if we simplify, we have the following:
![(3^2)^3\cdot3^x=3^6\cdot3^x=3^(x+6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/trw4f12vibbix5e3n8nytyedt8r6qfs19s.png)
and on the right side, we have:
![(3^7\cdot3^3)/(3^(11))=(3^(7+3))/(3^(11))=(3^(10))/(3^(11))=3^(10-11)=3^(-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/o7q0ed4gvfmusc2csobisp2pr0jdmgno8b.png)
then, if we equate both expression we have that:
![3^(x+6)=3^(-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/5p8hdr2393vxkuq32oayiv4swmreur2wlg.png)
then, this must mean that the exponents are equal. This means the following:
![x+6=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/ugab4uzkbkqfpk1s8alsd1uwk6gijumi6q.png)
solving for x we get:
![\begin{gathered} x+6=-1 \\ \Rightarrow x=-1-6=-7 \\ x=-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/3ugbahqqstn5r1c1xbc6hcetwlplbqe4ep.png)
therefore, x = -7